Stay Tuned! Assessing the Effectiveness of Social Media Video Ads - Steffen Schmidt; Andreas Thölke; Sascha Langner; Philipp Reiter; Nadine Hennigs; Michael Schießl (Marketing Review St.Gallen, 2016)
Advanced web technologies, especially social media channels, provide branding opportunities for companies to promote their brands for superior customer appeal. The present work shows the result of a real use case regarding the visibility and interaction performance of auto-play vs. click-to-play ads in affecting customers' mind.
Keywords: 650